2020
DOI: 10.5125/jkaoms.2020.46.4.258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of two phosphodiesterase inhibitors on bone healing in mandibular fractures (animal study in rats)

Abstract: Objectives: Despite advances in maxillofacial surgery, impaired bone healing remains a concern for surgical teams. Many studies have evaluated the effects of sildenafil and pentoxifylline on bone healing. However, their effects on healing of bone fractures have not been well investigated. This study aimed to assess the effects of the phosphodiesterase inhibitors sildenafil and pentoxifylline on healing of mandibular fractures in rats. Materials and Methods: A total of 60 rats were randomly divided into six gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The effects of drugs that affect bleeding and vascular permeability due to the hematoma stage in the inflammation period of fracture healing have been continuously investigated in the literature. Malekigorji et al 11 found that pentoxifylline and sildenafil (phosphodiesterase inhibitor), which are agents that increase vascular permeability, have a positive effect on bone healing in an experimental maxillofacial fracture model performed on rats. In an experimental study on nitric oxide, that increases vascular permeability, in a rat model, Diwan et al 12 They showed that fracture healing was delayed after nitric oxide inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of drugs that affect bleeding and vascular permeability due to the hematoma stage in the inflammation period of fracture healing have been continuously investigated in the literature. Malekigorji et al 11 found that pentoxifylline and sildenafil (phosphodiesterase inhibitor), which are agents that increase vascular permeability, have a positive effect on bone healing in an experimental maxillofacial fracture model performed on rats. In an experimental study on nitric oxide, that increases vascular permeability, in a rat model, Diwan et al 12 They showed that fracture healing was delayed after nitric oxide inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the existing pro-angiogenic factors have been successfully implemented within a clinical setting. Alternatively, therapies that increase perfusion through the endogenous vasculature may confer similar benefits as increased vascularization ( MalekiGorji et al, 2020 ). Existing approved drugs including (but are not limited to) sildenafil, tadalafil, nitroglycerin, epoprostenol, and iloprost have been shown to increase perfusion through vasodilation.…”
Section: Examples Of Targets Of Opportunitymentioning
confidence: 99%
“…Fracture healing could be a complex and moderate status of recovery controlled by an assortment of cytokines and stimulants. Osteoblast and osteoclast formation, apoptosis rate, and maintenance play a key role in fracture healing [ 6 ]. If there are problems with the proliferation, differentiation, and apoptosis of osteoblasts, the balance between bone formation and bone resorption will destroy, thus, bone healing will fail [ 7 ].…”
Section: Introductionmentioning
confidence: 99%